Overview of ionic liquids used as working fluids in absorption cycles [Book Chapter] - Khamooshi, Mehrdad; Parham, Kiyan; Atikol, U?ur (Apple Academic Press, 2014)
With fast economic growth and constantly increasing energy consumption, the human kind is about to face a growing degradation of the environment if business continues as usual. For this reason, the utilization of low-grade energy has become one of the most attractive solutions to heating and cooling problems encountered in industrial and residential applications. It is possible to recover the low-grade heat wasted in many industries to use it in some processes in order to increase the energy efficiency. © 2014 by Apple Academic Press, Inc.